Random fixed points for ∗-nonexpansive random operators. (2001) - Khan, Abdul Rahim; Hussain, Nawab
Abstract : The notion of a ∗ -nonexpansive multivalued map is different from that of a continuous map. In this paper we prove some fixed point theorems for ∗ -nonexpansive multivalued random operators in the setup of Banach spaces and Fréchet spaces. Our work generalizes, refines and improves the earlier results of a number of authors.